Effect of different neuromuscular training modalities on postural stability in healthy recreation people: a randomized controlled trial - Dragan Marinkovic; Drazenka Macak; Vukasin Stanic; Dejan M. Madic; Danilo Radanovic; Zoran Gojkovic; Miodrag Spasic; Aleksandra Ilic; Tatjana Trivic; Patrik Drid (Scientific Reports)
Abstract This study aimed to determine the effects of dynamic neuromuscular stabilization (DNS), whole-body vibration (WBV), and a combination of DNS and WBV (MIX) training modalities on postural stability (PS) in healthy recreation participants. The 179 participants (age 24.02 ± 2.07 years) were divided into the gender-balanced groups: MIX (n = 47), DNS (n = 45), WBV (n = 44), and control group (CONTROL, n = 43) and underwent two months treatment. The single and double-leg Center of Force (COF) parameters were collected. A 2 × 4 mixed-design analysis of covariances captured no changes from initial to final testing in all PS measures of WBV and CONTROL (p ≥ 0.30) and indicated trivial improvements (mean Hedge’s g) within the groups of the most PS measures (g≥-0.42, p ≤ 0.001). However, we noticed medium to large MIX and DNS improvements in left-leg COF (MIX: g ≤ 2.11; DNS: g ≤ 1.74) and double-leg COF (MIX: g ≤ 2.49; DNS: g ≤ 1.23). Contrast analysis further confirmed that MIX and DNS improved PS measures more than WBV and CONTROLS while showing higher improvements of MIX than DNS (mean difference in changes [95% Confidence Intervals]) in left-leg for 1.16 mm [0.37 mm, 1.95 mm] and double-leg COF for 0.67 mm [0.85 mm, 0.49 mm]. Combined DNS and WBV modalities expressed higher improvements in PS measures than single modalities and controls. However, further research is warranted to clarify the differences in DNS, WBV, and combined intervention effects on PS measures.